The Influence of Meme Content Exposure on Increasing Social Sensitivity and Critical Thinking Among College Students in Semarang City - Thuba Fahmi Ubaidillah; Made Dwi Adnjani (Program Studi Ilmu Komunikasi FBIK Unissula, 2026)
The development of social media has established memes as a dominant form of digital communication consumed by students. This study aims to analyze the influence of meme content exposure on the social sensitivity and critical thinking abilities of students in Semarang City. Using a positivistic paradigm, this research tests causal relationships based on Uses and Gratifications and Media Exposure theories. The research method utilizes a quantitative approach with a survey of 400 student respondents in Semarang selected through purposive sampling. Primary data were collected via questionnaires and analyzed using simple linear regression with IBM SPSS version 27 software. The results show that meme exposure has a positive and significant effect on students' social sensitivity (Sig. 0.000 < 0.05) with a regression coefficient of 0.720 and a coefficient of determination (R2) of 0.493. Furthermore, meme exposure also has a positive and significant effect on students' critical thinking (Sig. 0.000 < 0.05) with a regression coefficient of 0.531 and an R2 value of 0.281. These findings prove that memes are not merely entertainment media but are digital instruments capable of increasing social awareness and critical mindsets. The researcher recommends that higher education institutions optimize digital literacy so that students can utilize creative content more reflectively and wisely.